2020
DOI: 10.1038/s41598-020-72739-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of Intonation Units form a ~ 1 Hz rhythm

Abstract: Studies of speech processing investigate the relationship between temporal structure in speech stimuli and neural activity. Despite clear evidence that the brain tracks speech at low frequencies (~ 1 Hz), it is not well understood what linguistic information gives rise to this rhythm. In this study, we harness linguistic theory to draw attention to Intonation Units (IUs), a fundamental prosodic unit of human language, and characterize their temporal structure as captured in the speech envelope, an acoustic rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…Initial support suggests that syllable frequency across languages is confined to a narrow band between 4 and 8 Hertz (Ding et al, 2017;Coupé et al, 2019;Tilsen & Arvaniti, 2013), consistent with the previously proposed role of theta-band synchronization in syllable processing (Luo & Poeppel, 2007;Peelle et al, 2013;Doelling et al, 2014;Howard & Poeppel, 2012). Above the syllabic rate, a recent study found that the onset of intonation units that are analogous to ToBI's ip (Chafe, 1979;Du Bois, 1992) associates with a consistent phase angle of the speech envelope at a frequency of ∼1 Hertz (Inbar et al, 2020). This suggests that amplitude modulations at prosodic boundaries may indeed be sufficiently regular for synchronizing a periodic neuronal sampling mechanism.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Initial support suggests that syllable frequency across languages is confined to a narrow band between 4 and 8 Hertz (Ding et al, 2017;Coupé et al, 2019;Tilsen & Arvaniti, 2013), consistent with the previously proposed role of theta-band synchronization in syllable processing (Luo & Poeppel, 2007;Peelle et al, 2013;Doelling et al, 2014;Howard & Poeppel, 2012). Above the syllabic rate, a recent study found that the onset of intonation units that are analogous to ToBI's ip (Chafe, 1979;Du Bois, 1992) associates with a consistent phase angle of the speech envelope at a frequency of ∼1 Hertz (Inbar et al, 2020). This suggests that amplitude modulations at prosodic boundaries may indeed be sufficiently regular for synchronizing a periodic neuronal sampling mechanism.…”
Section: Introductionsupporting
confidence: 72%
“…While we studied a symbolic annotation of ips instead of their acoustics, ip boundaries are defined by multi-dimensional modulations, second in ToBI break index strength only to IP boundaries (Silverman et al, 1992;Pierrehumbert, 1980). In line with this, a subset of these cues, amplitude modulations at the boundaries of intonation units analogous to ips, are periodic at 1 Hertz (Inbar et al, 2020;Chafe, 1979;Du Bois, 1992). We extend this work here in two important ways.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations